Detection of petal colour QTLs in RILs of safflower: Detection of petal colour QTLs in RILs of safflower - K DIVYA; Y RUSHWANTH REDDY; KRISHNALATHA; J DHANUNJAY; V HEMALATHA; KADIRVEL PALCHAMY (Journal of Oilseeds Research, 2023)
The present study aimed to determine the QTL monitoring petal colour in F9 and F10 RILs derived from CO-1/EC-523368-2 safflower. Yellow, red and orange colours were observed in the population. QTL analysis determined five and three QTLs in F9 and F10 RILs respectively with 25.1 % as the highest phenotypic variance explained.